Udder and Teat Skin Lesions in Bovines - Sharma, Shukriti; Gupta, D. K.; Bansal, B. K. (International Journal of Livestock Research, 2020)
Udder and teat lesions are early indicators for increased risk of mastitis. It causes financial losses by decrease milk production, loss of quarter, reduced cost of animal and aesthetic value. The susceptibility to udder diseases is high among pure exotic breeds like HF, Jersey etc. followed by crossbreds. The resistance of local breeds of cattle and buffaloes to the infection is basically attributed to their lower milk production and a better immunity levels. The teat sphincter and teat canal are important primary barriers against pathogen invasion into the udder. Teat lesions, generally do not cause mastitis directly, but do interfere with the milking process and may cause secondary problems. These lesions are readily colonized by bacteria and thus serve as an important reservoir of infection. Economically, losses may be severe as animals usually resist milking and must be culled. In future mastitis research, understanding the way in which microorganisms penetrate the teat canal will become increasingly important. This review comprehends the clinical understanding of udder and teat lesions in dairy animals.